2022
DOI: 10.1088/1361-6501/ac8b9c
|View full text |Cite
|
Sign up to set email alerts
|

Automatic pointer meters recognition system based on line scan vision

Abstract: The automatic recognition of pointers is of great significance for efficiently collecting measurements from industrial instruments. In this paper, an automatic pointer meter recognition system based on line scan vision is developed. A line scan camera is used to capture images of the pointer of a pointer meter. Light-spot centroid algorithm is implemented to determine the centroid position of the pointer. The captured images can record the dynamic movement of the pointer, thereby enabling condition monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Calculate Meter Readings: The ultimate goal is an accurate calculation of the meter reading. Current methods for obtaining meter readings include the distance method [22], the angle method [44], the template method [45] and the depth regression method [46] to determine meter readings. Wang [47] used different states of the pointer in a linear scanner to calculate the parameters of the pointer translation function and predict the pointer reading based on the response obtained at the center of mass of the pointer's point of light and a given input amplitude.…”
Section: Related Workmentioning
confidence: 99%
“…Calculate Meter Readings: The ultimate goal is an accurate calculation of the meter reading. Current methods for obtaining meter readings include the distance method [22], the angle method [44], the template method [45] and the depth regression method [46] to determine meter readings. Wang [47] used different states of the pointer in a linear scanner to calculate the parameters of the pointer translation function and predict the pointer reading based on the response obtained at the center of mass of the pointer's point of light and a given input amplitude.…”
Section: Related Workmentioning
confidence: 99%
“…This system employs the light-spot centroid algorithm to accurately determine the central point of the meter's pointer. Trials have demonstrated that this method for extracting data from pointer meters exhibits remarkable resilience against various disturbances [3]. Ma et al, have introduced a highly precise and sturdy algorithm for the automatic reading of pointer meters.…”
Section: Introductionmentioning
confidence: 99%
“…Salomon et al [11] introduced a new data set in unconstrained scenarios, which improves the meter recognition rate combining YOLOv4 with a novel regression method (AngReg). Literature [2] developed an automatic pointer meter recognition system based on line scan vision. The captured image is used to record the dynamic movement of the pointer, and the centroid position of the pointer is determined by the optical spot centroid algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work on automatic pointer meter reading such as [2,[6][7][8][9][10][11] only addressed meter detection, pointer extraction and automatic reading content, and did not consider the problem of pointer meter reading in low illumination situations. And in the work of image enhancement such as [12][13][14][15][16][17][18][19] are targeted for natural images with low illumination, not combined with pointer meter reading, and most of the image enhancement networks are complex and time consuming affecting the reading efficiency.…”
Section: Introductionmentioning
confidence: 99%